KONSTRUKSI HUKUM LEMBAGA PENYELENGGARA PEMILIHAN UMUM DI INDONESIA DITINJAU DARI TEORI STUFENBAU - Haryanti, Dewi (Jurnal Pembaharuan Hukum, 2015)
The organizers of the elections are the institutions that hold elections. While the general election (hereinafter abbreviated as the election) is a means to realize the sovereignty of thepeople in the government of the Unitary State of the Republic of Indonesia in order to produce a democratic state government based on Pancasila and the 1945 Constitution of the State ofthe Republic of Indonesia.Election organizers are institutions that organize elections consisting of KPU, Bawaslu and DKPP which is a unified function of the election. The juridical basis for the establishment ofelection organizers is Pancasila, the 1945 Constitution of the Republic of Indonesia and the Law on Election Organizer. Furthermore, it is technically regulated through election management regulations such as PKPU,Perbawaslu, and DKPP Regulations. And other more technical provisions set forth in the Decision of the General Election Organizer and the Circulars.The appropriate legal theory for the establishment of election organizers is Stufenbau Theory which states that the legal systemis a tiered system of rules where the lowest legal norms shouldÂ  cling to higher legal norms, and the supreme law should cling to the most legal norms Fundamental (grundnorm). This can be seen from the juridical basis of the formation of electionorganizers are Pancasila as grundnormnya, the 1945 Constitution of NRI as its constitution, and the Law on election organizers.